2013
DOI: 10.1515/hf-2013-0129
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding for identification of the endangered species Aquilaria sinensis: comparison of data from heated or aged wood samples

Abstract: Aquilaria sinensis (Lour.) Gilg is an evergreen tree and produces agarwood used for incense and as a uniquely precious medicine. It is in danger of disappearing due to illegal logging and its identification and protection is crucial. However, it is difficult or impossible to distinguish A. sinensis from other species of the genus Aquilaria Lam. and its closely related genus Gyrinops Gaertn. based on wood anatomical characteristics. Probably, DNA barcoding technology might provide an improvement in species iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 11 publications
1
61
0
Order By: Relevance
“…Spreng. (Jiao et al 2014), members of the Meliaceae family (Michael et al 2012), Dalbergia odorifera T.C. Chen (Yu et al 2016), Robinia pseudoacacia L. (De Filippis and Magel 1998), Quercus L. ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Spreng. (Jiao et al 2014), members of the Meliaceae family (Michael et al 2012), Dalbergia odorifera T.C. Chen (Yu et al 2016), Robinia pseudoacacia L. (De Filippis and Magel 1998), Quercus L. ssp.…”
Section: Introductionmentioning
confidence: 99%
“…The extraction of sapwood DNA followed the DNeasy Plant Mini Kit (Qiagen, Hilden, Germany) protocol according to Jiao et al (2014). The 2-μg DNA sample was subjected to quality checks before next-generation sequencing (NGS) using a Qubit fluorometer with a Quant-iT dsDNA BR assay kit (Thermo Fisher Scientific, Waltham, MA, USA) and agarose gel electrophoresis assay.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies reported that the less potential inhibitors of DNA isolation and PCR amplification are present in the sapwood (Rachmayanti et al 2006;Tnah et al 2012;Yu et al 2016). There are many more living parenchyma cells in the sapwood than in the heartwood (Jiao et al 2014;Yu et al 2016). Thus, the six InDel primers are useful for wood differentiation between C. micranthum and C. kanehirae and can be helpful in forensic investigations in the court.…”
Section: Indel Predictions and Identification Of C Micranthum And Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the region of nuclear ribosomal internal transcribed spacer (ITS) and the ITS2 region were also suggested as an alternative source of barcoding for flora (Chen et al 2010a;China Plant BOL Group 2011). Single or combined barcodes allows the identification of different species for a number of genera (Ibeiro et al 2007;Gonzalez et al 2009;Chen et al 2014;Jiao et al 2014). Hassold et al (2016) demonstrated that DNA barcoding is efficient to discriminate between Malagasy and non-Malagasy Dalbergia species.…”
Section: Introductionmentioning
confidence: 99%